Controlled synthesis of few-layer SnSe2 by chemical vapor deposition. Issue 69 (19th November 2020) - An, Boxing; Ma, Yang; Zhang, Guoqing; You, Congya; Zhang, Yongzhe
Abstract : Few-layer SnSe2 has intrinsic low thermal conductivity and unique phase transition from amorphous to crystalline state under laser irradiation. Abstract : Few-layer SnSe2 has intrinsic low thermal conductivity and unique phase transition from amorphous to crystalline state under laser irradiation. It has been extensively used in the fields of thermoelectric conversion and information storage. However, the traditional precursors like tin oxide and organic compounds have either high melting points or complex compositions, and the improper deposition temperature of the substrate may lead to mixed products, which impedes controllable synthesis of high-quality few-layer SnSe2 . Here, we propose a chemical vapor deposition (CVD) method, in which the precursor evaporation and deposition have been controlled via the adjustment of precursors/substrate positions, which effectively avoided mixed product growth, thus achieving the growth of high-quality few-layer SnSe2 . The calculated first-order temperature coefficient of the A1g module is −0.01549 cm −1 K −1, which is superior to other two-dimensional (2D) materials. Meanwhile, two exciton emissions from few-layer SnSe2 have been found, for which the higher energy one (1.74 eV) has been assigned to near-band-gap emission, while the lower one (1.61 eV) may have roots in the surface state of SnSe2 . The few-layer SnSe2 also exhibits large exciton binding energies (0.195 and 0.177 eV), which are greater than those of common semiconductors and may contribute to stability of excitons, showing broad application prospects in the field of optoelectronics.